2016
DOI: 10.1111/hae.13062
|View full text |Cite
|
Sign up to set email alerts
|

Relative contributions of bleeding scores and iron status on health‐related quality of life in von Willebrand disease: a cross‐sectional study

Abstract: This study is the first to examine the impact of VWD on HR-QoL across disease severity while incorporating socioeconomic status and rurality. Significant reductions in HR-QoL among VWD patients, especially the relationship between iron status and mental HR-QoL, strengthen the rationale for prospective studies to evaluate the efficacy of iron replacement in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(63 citation statements)
references
References 36 publications
1
62
0
Order By: Relevance
“…Compared with normative data, women with VWD reported significant reductions ( P < .05) in all domain components except “role emotional,” including vitality, mental health, and mental component summary; iron deficiency was one of the contributory factors. 40 The mental component score was also reduced compared with controls in women diagnosed as hemophilia carriers and in the subgroup with a bleeding tendency ( P = .05 for both comparisons); however, there were no significant differences in the individual domains. 36 In 355 people with VWD recruited to a French study, the mental component summary score at baseline was lower among women than men (no statistical significance was reported).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Compared with normative data, women with VWD reported significant reductions ( P < .05) in all domain components except “role emotional,” including vitality, mental health, and mental component summary; iron deficiency was one of the contributory factors. 40 The mental component score was also reduced compared with controls in women diagnosed as hemophilia carriers and in the subgroup with a bleeding tendency ( P = .05 for both comparisons); however, there were no significant differences in the individual domains. 36 In 355 people with VWD recruited to a French study, the mental component summary score at baseline was lower among women than men (no statistical significance was reported).…”
Section: Resultsmentioning
confidence: 89%
“…Thirteen studies reported mental health outcomes. 19 , 20 , 22 , 23 , 24 , 26 , 30 , 31 , 32 , 35 , 36 , 37 , 40 …”
Section: Resultsmentioning
confidence: 99%
“…17 Smaller studies performed in Canada (102 patients, SF-36 questionnaire), Finland (47 patients, Medical Outcomes Study-36 questionnaire), Sweden (30 female patients, SF-36 questionnaire), Canada again (28 patients, Health Utility Index Mark-2 and Mark-3) or United Kingdom (57 female patients, general questionnaire) not only confirmed a lower quality of life for VWD patients compared to the general population, but for studies in which both men and women were included, most reported a difference between both genders. [18][19][20][21][22] Studies focusing primarily on women clearly indicate how the burden of VWD is borne disproportionately by women. Heavy menstrual bleeding and its associated pain (observed in 32-100% of patients), 23 post-partum hemorrhage (in 15-60% of patients), 13 and hysterectomy (performed in 10-26% of patients), 24 are common in VWD women.…”
Section: Vwd and Quality Of Lifementioning
confidence: 99%
“…Clinical manifestations of VWD include mucocutaneous bleeding such as mouth and nose bleeds, gastrointestinal bleeds, joint bleeds, and menorrhagia [16], and bleeding severity can vary depending on the disease type. Patients with severe VWD (mostly type 2 and 3) may suffer from recurrent bleeding, with a potential negative impact on quality of life [15,[17][18][19][20]. In addition, in patients with recurrent joint bleeding, the detrimental effect on long-term joint outcomes may be comparable with moderate/severe hemophilia [19].…”
Section: Introductionmentioning
confidence: 99%